Laboratory evaluation and prognostication among adults and children with CEBPA‐mutant acute myeloid leukemia. (20th July 2021) - Mendoza, Hadrian; Podoltsev, Nikolai A.; Siddon, Alexa J.
Abstract: CEBPA ‐mutant acute myeloid leukemia (AML) encompasses clinically and biologically distinct subtypes of AML in both adults and children. CEBPA ‐mutant AML may occur with monoallelic (mo CEBPA ) or biallelic (bi CEBPA ) mutations, which can be somatic or germline, with each entity impacting prognosis in unique ways. Bi CEBPA AML is broadly associated with a favorable prognosis, but differences in the type and location of CEBPA mutations as well as the presence of additional leukemogenic mutations can lead to heterogeneity in survival. Concurrent FLT3‐ITD mutations have a well‐documented negative effect on survival in adult bi CEBPA AML, whereas support for a negative prognostic effect of mutations in TET2, DNMT3A, WT1, CSF3R, ASXL1, and KIT is mixed. NPM1 and GATA2 mutations may have a positive prognostic impact. Mo CEBPA AML has similar survival outcomes compared to AML with wild‐type CEBPA, and risk stratification is determined by other cytogenetic and molecular findings. Germline CEBPA mutations may lead to familial bi CEBPA AML after acquisition of second somatic CEBPA mutation, with variable penetrance and age. Bi CEBPA AML in children is likely a favorable‐risk diagnosis as it is in adults, but the role of a single CEBPA mutation and the impact of concurrent leukemogenic mutations are not clear in this population. Laboratory evaluation of the CEBPA gene includes PCR‐based fragment‐length analysis, Sanger sequencing, and next‐generation sequencing. Phenotypic analysis using multiparameter flow cytometry can also provide additional data in evaluating CEBPA, helping to assess for the likelihood of mutation presence.